Model Monitoring Detak Jantung Berbasis Smartphone Menggunakan Nodemcu Esp8266 - Ahmad Sahril Asmi; Bahar Bahar (Progresif: Jurnal Ilmiah Komputer, 2023)
Previous research used an Arduino microcontroller which was connected to a Bluetooth network, resulting in a limited connection distance for presenting data from the detection of heartbeats. This article presents the use of Nodemcu as a device for monitoring heart rate remotely via a smartphone network. A Pulse Sensor is attached to certain body parts to detect the patient's heart rate. Detection results are presented on a display attached to the detector device, also transmitted via the internet network to connect to the smartphone display via the Nodemcu8266 device. Testing is carried out in 2 ways, namely the accuracy of the Pulse Sensor in detecting heartbeats, carried out by comparing the results of the Pulse Sensor's work with a standard heart rate reader (Oximeter); and testing smartphone network connection. The results of the Pulse Sensor test show that there is only a difference of 1 to 4 bpm with the results of the Oximeter detection (98.33% accuracy), while testing the display of Pulse Sensor reading results on Smartphones via an internet network connection, is best on a network speed of 27 Mbps (accuracy reaches 98.04%) ).Keywords: Pulse Sensor; Nodemcu; Internet Network; Smartphones AbstrakPenelitian terdahulu menggunakan mikrokontroler Arduino yang di hubungkan dengan jaringan bluetooth, menghasilkan jarak koneksi penyajian data hasil deteksi detak jantung secara terbatas. Artikel ini menyajikan penggunaan Nodemcu sebagai perangkat untuk memonitoring detak jantung secara jarak jauh melalui jaringan smartphone. Sebuah Pulse Sensor ditempelkan pada bagian tubuh tertentu untuk mendeteksi detak jantung pasien. Hasil deteksi disajikan pada display yang melekat pada perangkat detektor, juga ditransmisikan melalui jaringan internet untuk terkoneksi ke display smartphone melalui perangkat Nodemcu8266.  Pengujian dilakukan dalam 2 hal, yaitu keakuratan Pulse Sensor dalam mendeteksi detak jantung, dilakukan dengan membandingkan hasil kerja Pulse Sensor dengan alat pembaca detak jantung standar (Oximeter); dan pengujian koneksi jaringan smartphone. Hasil uji Pulse Sensor menunjukkan hanya terdapat perbedaan 1 hingga 4 bpm dengan hasil deteksi Oximeter (akurasi 98,33%), sedangkan pengujian display hasil pembacaan Pulse Sensor pada Smartphone melalui koneksi jaringan internet, terbaik terjadi pada jaringan berkecepatan 27 Mbps (akurasi mencapai 98.04%).Kata Kunci: Pulse Sensor; Nodemcu; Jaringan Internet; Smartphone